Desenvolvimento estratégico de sites e plataformas para o Grupo Jazzy - Runge, Michelle Fernandes (2021)
Submitted by Susana Santos (susana.santos@universidadeeuropeia.pt) on 2021-02-02T16:47:27Z No. of bitstreams: 1 Tese Michelle Fernandes Runge - Design Management_compressed.pdf: 4987289 bytes, checksum: 441648f57e58b31a642f346f3047f248 (MD5)